Hubungan Durasi Penggunaan Mouthpiece SCUBA Diving dengan Gangguan Sendi Temoporomandibular pada Penyelam Ditpolairud Sulawesi Utara - Ratrianissa, Renia; Mariati, Ni Wayan; Pangemanan, Damajanty H. C. (e-GiGi, 2025)
Abstract: Temporomandibular joint (TMJ) disorders are musculoskeletal problems with high prevalence, especially in Southeast Asia. The use of mouthpieces during SCUBA diving for long duration is at risk of causing oral trauma, local inflammation, and dysfunction of the TMJ and masticatory muscles. Studies have shown a correlation between repeated use of mouthpieces and post-dive jaw or neck pain, especially in military divers such as members of Direktorat Kepolisian Air dan Udara (Ditpolair) North Sulawesi who are often exposed to similar conditions. This was an observational study with a cross sectional design. Respondents were 30 members of Ditpolairud North Sulawesi who met the eligibility criteria. The chi-square test was used to calculate the correlation between duration and temporomandibular joint disorders. The results showed that the majority of respondents were 17-30 years (53.3%), the duration of diving obtained the same results (50%) in both time periods. Most subjects (63.3%) were found to have temporomandibular joint disorders. The chi-square obtained a p-value of 0.058. In conclusion, there is no relationship between the duration of use of SCUBA diving mouthpieces and temporomandibular joint disorders in divers of the North Sulawesi Ditpolairud. Keywords: mouthpiece SCUBA; temporomandibular joint disorder; divers Abstrak: Gangguan senditemporomandibular (TMJ) merupakan masalah muskuloskeletal dengan prevalensi tinggi, terutama di Asia Tenggara. Penggunaan mouthpiece saat SCUBA diving dalam durasi lama berisiko menyebabkan trauma mulut, inflamasi lokal, serta disfungsi TMJ dan otot mastikasi. Studi menunjukkan korelasi antara penggunaan berulang mouthpiece dan nyeri rahang atau leher pasca penyelaman, terutama pada penyelam militer yang sering terpapar kondisi serupa. Penelitian ini menggunakan metode observasional dengan desain potong-lintang. Responden ialah 30 anggota Direktorat Kepolisian Air dan Udara (Ditpolair) Sulawesi Utara yang memenuhi kriteria eligibilitas. Uji chi-square digunakan untuk menghitung korelasi antara durasi dan gangguan TMJ. Hasil penelitian mendapatkan mayoritas responden berusia 17-30 tahun (53,3%), durasi penyelaman responden didapatkan hasil yang sama (50%) pada kedua periode waktu. Sebagian besar responden (63,3%) mengalami gangguan TMJ. Hasil uji chi-square mendapatkan nilai p=0,058 yang menunjukkan hubungan tidak bermakna. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara durasi penggunaan mouthpiece SCUBA diving dengan gangguan sendi temoporomandibular pada penyelam Ditpolairud Sulawesi Utara. Kata kunci: mouthpiece SCUBA diving; gangguan sendi temporomandibular; penyelam